Developing a Community-Based Digital Branding Ecosystem for Kampung Keren Tourism at Sumber Banteng, Kediri - Munawaroh, Nuril Aullia; Ambarwati, Diana; Sa'adillah S.A.P, Rangga; Ilham, Moh. (Jurnal Soeropati, 2025)
This community service project aims to enhance the digital promotion of Kampung KEREN Sumber Banteng, Kediri, a high-potential tourism village with low digital visibility. Key challenges include unintegrated digital channels, a lack of structured storytelling, big77 and limited capacity in content management. The program implements a community-based digital branding ecosystem by integrating platforms like Instagram, Website, Google Maps, WhatsApp Business, and Linktree. Using a participatory approach, local tourism actors (Pokdarwis and UMKM) were involved in planning, training, and implementation. Based on the visitor journey and local storytelling, the project led to improved digital presence, enhanced content creation skills, and the emergence of user-generated content (UGC). This initiative offers a replicable model for digital branding in tourism villages and highlights digital marketing's role in empowering local communities.